Clinical and epidemiological profile of elderly patients seen in a hypertensive emergency at a public hospital in the state of Rio de Janeiro – Hypertensive emergency in the elderly - de Senne, Júlia A.; de Oliveira, Igor Fernando S.; Oliveira, Karolina de S.; Rangel, Maria Eduarda A.; Raimundo, Raphael F. de O.; Oliveira, Rodrigo W. de; Tenorio, Vitor (Brazilian Journal of Health and Biomedical Sciences, 2022)
Introduction: Hypertensive emergencies (HE) are clinical entities characterized by an acute and significant increase in blood pressure (BP) associated with severe symptoms that evidence target organ damage. Objective: To analyze the clinical and epidemiological profile of elderly patients treated in a hypertensive emergency at a public hospital in the state of Rio de Janeiro. Method: This study is prospective and descriptive. Information was collected from August to October, 2020 using medical records and processed using the Statistic Statsoft program. Pearson’s test was performed for univariate analysis. Results: The sample consisted of 109 patients. The average age found was 73 years old, with a predominance of males (69.72%) and brown skin (36.69%). Approximately 72.48% of the patients had a history of Systemic Arterial Hypertension (SAH), however, (50.46%) reported that they did not regularly use antihypertensive medication. Target organ injuries were ischemic stroke (58.71%), followed by acute coronary syndrome (24.77%), hemorrhagic stroke (9.17%) and edema acute lung disease (7.33%). Regarding the BP values found at admission, the mean systolic pressure was 205.0 mmHg, while the mean diastolic pressure was 127.0 mmHg. Conclusion: Ischemic stroke was the most frequent HE in the sample. It is necessary to put in place measures to prevent risk factors associated with SAH, as well as to control blood pressure levels to reduce the number of consultations due to hypertensive emergencies and other complications of cardiovascular diseases. Keywords: Emergency; Hypertension; Prevalence.